Two-Dimensional Electronics and Optoelectronics - Zhixian Zhou (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The discovery of monolayer graphene led to a Nobel Prize in Physics being awarded in 2010. This has stimulated further research on a wide variety of two-dimensional (2D) layered materials. The coupling of metallic graphene, semiconducting 2D transition metal dichalcogenides (TMDCs) and black phosphorus have attracted a tremendous amount of interest in new electronic and optoelectronic applications. Together with other 2D materials, such as the wide band gap boron nitride nanosheets (BNNSs), all these 2D materials have led towards an emerging field of van der Waal 2D heterostructures. The papers in this book were originally published by Electronics (MDPI) in a Special Issue on "Two-Dimensional Electronics and Optoelectronics". The book consists of eight papers, including two review articles, covering various pertinent and fascinating issues concerning 2D materials and devices. Further, the potential and the challenges of 2D materials are discussed, which provide up to date guidance for future research and development.